2017
DOI: 10.1073/pnas.1705165114
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cells induce interleukin-22 production from memory CD4+T cells via interleukin-1 to promote tumor growth

Abstract: IL-22 has been identified as a cancer-promoting cytokine that is secreted by infiltrating immune cells in several cancer models. We hypothesized that IL-22 regulation would occur at the interface between cancer cells and immune cells. Breast and lung cancer cells of murine and human origin induced IL-22 production from memory CD4 T cells. In the present study, we found that IL-22 production in humans is dependent on activation of the NLRP3 inflammasome with the subsequent release of IL-1β from both myeloid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
128
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 61 publications
(65 reference statements)
3
128
0
Order By: Relevance
“…Patients and samples CM tissues, adjacent normal tissues and peripheral blood were collected from 30 patients diagnosed with CM according to clinical and histological manifestation in department of dermatology, the Affiliated Hospital of Southwest Medical University (Based on the expression of interleukin 22 in normal human tissues and other tumor tissues obtained from published report 18,19 , we statistical estimated sample size in our study, and found that 30 cases enrolled in both patient group and health group could meet the statistical requirement.). They are 40-60 years old with 17 male and 13 female.…”
Section: Methodsmentioning
confidence: 99%
“…Patients and samples CM tissues, adjacent normal tissues and peripheral blood were collected from 30 patients diagnosed with CM according to clinical and histological manifestation in department of dermatology, the Affiliated Hospital of Southwest Medical University (Based on the expression of interleukin 22 in normal human tissues and other tumor tissues obtained from published report 18,19 , we statistical estimated sample size in our study, and found that 30 cases enrolled in both patient group and health group could meet the statistical requirement.). They are 40-60 years old with 17 male and 13 female.…”
Section: Methodsmentioning
confidence: 99%
“…34 IL-1 signaling has also been associated with increased chemoresistance in mouse models of cancer 35 and production of protumorigenic IL-22. 36 In prognostic studies, higher tumor IL-1β levels have been associated with improved survival of patients with lymph node-positive breast cancer, 37 while the use of a blocking anti-IL-1β antibody in patients with cardiovascular diseases showed a reduction on lung cancer incidence. 38 Extracellular ATP activates NLRP3 inflammasome through P2×7 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…We were able to validate the presence of IL-22 in lavages of lung cancer patients and other pulmonary diseases (16). Along these lines, murine breast cancer cells showed a reduction in tumor growth accompanied by a decreased IL-22 expression after administration of IL-1 blocking agents (9), illustrating the close connection between these two cytokines, each representing a different cytokine family. Nevertheless, the role of IL-22 on the progression of lung cancer remains elusive and will need to be further investigated.…”
mentioning
confidence: 70%
“…Moreover, recent studies have demonstrated the importance of IL-1 signaling for sustaining the immunosuppressive capacities of TAM (14). In the Pointing to another mechanism, we could recently show the involvement of IL-1-dependent up-regulation of interleukin-22 expression (IL-22) in murine and human breast and lung cancer models (9). IL-22 is, among other important functions, involved in tissue repair mechanisms and induces signal transducer and activator of transcription-3-dependent (STAT3) proliferative signaling cascades (15).…”
mentioning
confidence: 92%
See 1 more Smart Citation